An automated garden irrigation system: Controlled and monitored via Arduino and Lab-VIEW - Gogoi, M.N (International Journal of Computer Sciences and Engineering, 2025)
This paper proposed an efficient method of irrigation system for farmer so that they utilized water resource in a proper manner. This method is cost effective, reduced traditional method of irrigation system, low power consumption, and eliminate human intervention. The main aspect of our paper is to determine the soil moisture at some instant of intervals in its dry and wet condition with the aid of soil moisture circuit, evaluate the equivalent moisture and irrigate it based on nature. So the proposed system uses Arduino UNO development board and Lab-VIEW. It is programmed in such way that the sensors that is soil moisture sensor and water level sensor will sense moisture content of the soil and water level of the water storage and fed to Arduino, accordingly it will send command signal to pump to switch ON/OFF based on condition provided by the sensors. For better visualization of the sensors values to farmer, a graphical user interface is developed in LAB-VIEW . The various conditions will be indicated on the front panel such as wet and dry condition of soil with the level of water in the tank